Implementasi Penerapan Budaya Kaizen dalam Meningkatkan Mutu Pendidikan di Sekolah - Rani Irmayanti (STIT Fatahillah, 2024)
When we want change in our lives, we often expect immediate and drastic changes. We hope that this change will soon have a significant impact on our lives. But usually, we focus too much on results, don't commit to long-term changes, and the results are not optimal. Apart from building motivation and strong intentions, you must also develop habits and continuous improvement. Things like this are known based on the Japanese cultural principle of